Precious metal-based carbon monoxide oxidation catalyst as well as preparation method and application thereof
By loading highly dispersed Pt and/or Pd metal particles on the hydrotalcite support, Pt/Pd-M alloy particles are formed, which solves the problem of inactivation of precious metal catalysts in the sulfide environment, and achieves efficient oxidation and removal of carbon monoxide and good catalytic stability.
Patent Information
- Application Number
- CN202311370327.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-10-20
AI Technical Summary
Existing precious metal catalysts are prone to inactivation in sulfide-containing environments, and it is difficult to take into account high carbon monoxide oxidation activity and good sulfur resistance stability.
The carrier is prepared by the topological transformation method of hydrotalcite structure, and the highly dispersed Pt and/or Pd metal particles are loaded to form Pt/Pd-M alloy particles, and the stability of the catalyst is improved by using metal-support interaction.
High-efficiency oxidation and removal of carbon monoxide in the presence of hydrogen sulfide was achieved. The CO conversion rate of the catalyst remained above 99% after 200 hours of reaction time, significantly extending the life of the catalyst.
Smart Images

Figure CN119857494A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbon monoxide oxidation catalysts, and in particular to a noble metal-based carbon monoxide oxidation catalyst and a preparation method and application thereof. Background Art
[0002] Carbon monoxide is one of the common pollutants in the atmosphere, commonly known as coal gas. It is colorless, odorless, tasteless, non-irritating, highly toxic, and not easily liquefied or solidified. The main source of carbon monoxide is the product of incomplete combustion of carbon-containing substances. Industrial furnaces and civilian boilers, stoves, as well as internal combustion engines and automobile exhaust are the main sources of carbon monoxide pollution. Extremely low concentrations of carbon monoxide can enter the human body through the respiratory tract and cause poisoning. Therefore, controlling the concentration of carbon monoxide in the atmospheric environment is of great significance to human survival and health and environmental protection.
[0003] In some chemical production processes, the tail gas produced contains low-concentration CO gas (<20000ppm). For this type of tail gas, the recovery cost is relatively high. In order to meet emission requirements, adsorption, photocatalysis, low-temperature plasma conversion, combustion and other methods are usually used to remove CO. Among them, the catalytic oxidation method introduces a high-efficiency catalyst on the basis of the combustion method to reduce the temperature of the combustion process. It has the advantages of simple process and high removal efficiency, and therefore has received widespread attention. At present, there are many public reports on catalysts for the catalytic oxidation of low-concentration CO, usually using precious metals such as Pt and Au as active components. However, the CO-containing exhaust gas of many chemical plants usually contains low-concentration sulfides (<50ppm, including H 2 S, COS, etc.). Such sulfur-containing compounds have a strong poisoning effect on precious metal catalysts and can easily lead to catalyst deactivation. The development of precious metal catalysts that take into account both high carbon monoxide oxidation activity and good sulfur-resistant reaction stability has become an important development direction for catalysts.
[0004] Hydrotalcite, also known as layered dihydroxy composite metal hydroxide, is a layered material composed of two metal hydroxides. Because of its structural characteristics such as atomic-level dispersion of metal atoms in the layer plate, adjustable metal cation types and intercalated anion types, confinement effect and memory effect, it can be used to construct a variety of inorganic functional materials. In recent years, the preparation of supported metal catalysts by topological transformation of the structure of hydrotalcite layered metal hydroxide has become a new hot spot for the utilization of hydrotalcite. This method uses the layered structure of hydrotalcite as a precursor, and with the help of its lattice positioning effect, the high dispersion of metal cations in the main layer plate and the advantages of oriented arrangement of interlayer anions, after calcining / reducing the hydrotalcite, a high-performance catalytic material with preferential orientation of active sites, high dispersion and stable dispersion can be obtained. The catalytic material prepared with hydrotalcite as a precursor has also been applied in the carbon monoxide oxidation reaction. Patent application CN106881110A uses a three-step method of coprecipitation, deposition and precipitation liquid phase reduction to prepare a palladium catalyst suitable for carbon monoxide oxidation in the coexistence of water and vapor. The palladium precursor is loaded on the surface of the pre-prepared nickel-aluminum hydrotalcite by a deposition precipitation method, and then the metal palladium particles with an average particle size of 1.4nm are obtained by a sodium borohydride liquid phase reduction method. The catalyst shows good stability in the carbon monoxide oxidation reaction under the coexistence of water vapor. Patent application CN107649129B discloses a method for preparing a monolithic structured gold catalyst. In the preparation process of the monolithic structured gold catalyst, a metal oxide hydrotalcite nanosheet layer is first epitaxially grown on the monolithic structured substrate to form a monolithic structured carrier, and then nano-gold particles are loaded on the monolithic structured carrier. The catalyst shows good low-temperature activity in the carbon monoxide oxidation reaction.
[0005] Through summary, it is found that catalysts prepared with hydrotalcite structure or its topological structure can show good reactivity in oxidation reactions. However, in the face of complex real industrial waste gas environment, it is necessary to consider the reaction stability of the catalyst in the presence of poisons such as sulfide. Summary of the invention
[0006] The purpose of the present invention is to provide a noble metal-based carbon monoxide oxidation catalyst and its preparation method and application for the treatment of tail gas containing low concentration CO in industrial production processes including coal chemical industry, in order to improve the catalytic stability of the catalyst in the presence of sulfide (such as hydrogen sulfide, etc.). In the present invention, the active metal Pt and / or Pd is obtained by loading a carrier with high dispersion of metal additives obtained by topological transformation of the hydrotalcite structure. Specifically, first, the M-Mg-Al ternary hydrotalcite is prepared by coprecipitation method, and the metal additive M is highly dispersed at the atomic level; then, by controlling the roasting conditions, a carrier with a layered topological structure of hydrotalcite is formed; then, by controlling the pH of the impregnation solution, the active metal platinum precursor is introduced into the gap of the carrier layered structure, and then roasting-reduction is performed to form a supported catalyst with highly dispersed Pt / Pd-M alloy particles. In the preparation method, the unique laminar confinement effect and memory effect of the hydrotalcite structure are utilized to make the obtained metal alloy particles have a smaller average particle size and a unique surface structure, and at the same time form a stronger metal-carrier interaction. The catalyst exhibits good catalytic activity in the carbon monoxide oxidation reaction and has a low activation temperature. It also exhibits good catalytic stability in an atmosphere containing hydrogen sulfide.
[0007] In order to achieve the above-mentioned object, the present invention provides a noble metal-based carbon monoxide oxidation catalyst, comprising a carrier and an active component supported on the carrier, wherein the active component is Pt and / or Pd, and the carrier is formed by calcining and reducing M-Mg-Al ternary hydrotalcite, wherein M is at least one of Fe, Co, Ni, Zn, Cu and Cr, and Pt and / or Pd form alloy particles with M.
[0008] Preferably, based on the total weight of the noble metal-based carbon monoxide oxidation catalyst, the content of Mg as oxide is 10-40 wt %, the content of Al as oxide is 20-60 wt %, the content of M as oxide is 0.5-10 wt %, and the content of Pt and / or Pd as metal elements is 0.1-1 wt %.
[0009] The present invention also provides a method for preparing a noble metal-based carbon monoxide oxidation catalyst, the method comprising the following steps:
[0010] (1) preparing M-Mg-Al ternary hydrotalcite, wherein M is at least one of Fe, Co, Ni, Zn, Cu and Cr;
[0011] (2) calcining the M-Mg-Al ternary hydrotalcite;
[0012] (3) mixing the hydrotalcite material calcined in step (2) with an aqueous solution of a noble metal precursor, and then separating a solid material;
[0013] (4) calcining the solid material obtained in step (3);
[0014] (5) reducing the powder obtained after calcination in step (4).
[0015] Preferably, in step (1), the M-Mg-Al ternary hydrotalcite is prepared by a co-precipitation method.
[0016] Preferably, the precipitant used is urea or a mixture of sodium carbonate and sodium hydroxide.
[0017] Preferably, the metal salt precursor used is nitrate and / or chloride, preferably nitrate.
[0018] Preferably, in step (2), the calcination conditions include: temperature of 200-500° C. and time of 3-6 h.
[0019] Preferably, in step (3), the noble metal precursor is at least one of chloroplatinic acid, platinum chloride, platinum nitrate, platinum acetylacetonate, palladium chloride, palladium nitrate and palladium acetate.
[0020] Preferably, the specific operation process of step (3) is: dispersing the hydrotalcite material in the aqueous solution of the noble metal precursor, adjusting the pH value of the obtained suspension to 5-9, then stirring in a constant temperature water bath for 5-48 hours, separating the solid, washing and drying.
[0021] Preferably, the temperature of the constant temperature water bath is 60-90°C.
[0022] Preferably, the specific operation of step (4) is: heating the solid material to 400-600° C. at a heating rate of 1-3° C. / min, and calcining for 3-6 hours.
[0023] Preferably, in step (5), the reduction process is carried out in an atmosphere containing hydrogen and a protective gas, wherein the content of hydrogen in the atmosphere containing hydrogen and a carrier gas is 8-15 vol%.
[0024] Preferably, the reduction conditions include: temperature of 300-500° C. and time of 1-3 h.
[0025] The present invention also provides a noble metal-based carbon monoxide oxidation catalyst prepared by the method.
[0026] The present invention also provides the use of the noble metal-based carbon monoxide oxidation catalyst as a catalyst for carbon monoxide oxidation reaction.
[0027] Preferably, the reaction raw gas used in the carbon monoxide oxidation reaction contains sulfides below 50 ppm.
[0028] The technical solution of the present invention has the following advantages:
[0029] (1) Compared with other carbon monoxide oxidation catalysts, the noble metal-based carbon monoxide oxidation catalyst of the present invention can achieve sulfide (such as H 2 S) is highly selectively oxidized to sulfur dioxide, reducing the adsorption and deposition of sulfides on the catalyst and extending the catalyst life.
[0030] (2) Compared with other carbon monoxide oxidation catalysts, the noble metal-based carbon monoxide oxidation catalyst of the present invention has a higher performance in sulfides (such as H 2 S) showed good catalytic stability, specifically, at a space velocity of 10000 h -1 , reaction temperature 250°C, inlet CO concentration 6000ppm and the presence of 50ppm hydrogen sulfide, after 200h reaction time, the CO conversion rate still remained above 99%.
[0031] The noble metal-based carbon monoxide oxidation catalyst of the present invention has a simple composition, excellent performance, and has industrial application prospects. Relying on the catalyst of the present invention, a low-concentration carbon monoxide catalytic removal technology can be formed, which is suitable for a variety of low-concentration carbon monoxide removal conditions including the presence of sulfides, and can reduce the carbon monoxide concentration in the tail gas to below 50ppm. It can be widely used in tail gas treatment in petrochemical, steel, industrial kilns, garbage incineration and other processes, and is of great significance for protecting the atmospheric environment and ensuring human health. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The catalyst PtFe / MgAlO in Example 1 x A graph of catalytic oxidation CO conversion;
[0033] Figure 2 The catalyst PtFe / MgAlO in Example 1 x SEM and TEM images of
[0034] Figure 3 The catalyst PtFe / MgAlO in Example 1 x HRTEM and STEM-HAADF images;
[0035] Figure 4 The catalyst Pt / Fe / MgAlO in Comparative Example 1 x TEM image of. DETAILED DESCRIPTION
[0036] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0037] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0038] The noble metal-based carbon monoxide oxidation catalyst of the present invention comprises a carrier and an active component supported on the carrier, wherein the active component is Pt and / or Pd, and the carrier is formed by calcining and reducing M-Mg-Al ternary hydrotalcite, wherein M is at least one of Fe, Co, Ni, Zn, Cu and Cr, and Pt and / or Pd form alloy particles with M (i.e., Pt / Pd-M alloy particles).
[0039] In the noble metal-based carbon monoxide oxidation catalyst of the present invention, Pt / Pd-M alloy particles are highly dispersed in the catalyst, and the average particle size of the Pt / Pd-M alloy particles is 4-8 nm.
[0040] In the precious metal-based carbon monoxide oxidation catalyst of the present invention, based on the total weight of the precious metal-based carbon monoxide oxidation catalyst, the content of Mg in terms of oxide may be 10-40% by weight, preferably 25-40% by weight; the content of Al in terms of oxide may be 20-60% by weight, preferably 40-60% by weight; the content of M in terms of oxide may be 0.5-10% by weight, preferably 1-8% by weight; the content of Pt in terms of metal element may be 0.1-1% by weight, preferably 0.5-0.8% by weight.
[0041] The noble metal-based carbon monoxide oxidation catalyst of the present invention can still stably carry out the carbon monoxide oxidation removal process in the presence of hydrogen sulfide, and can take into account both catalytic oxidation activity and sulfur-resistant reaction stability.
[0042] The method for preparing the noble metal-based carbon monoxide oxidation catalyst of the present invention comprises the following steps:
[0043] (1) preparing M-Mg-Al ternary hydrotalcite, wherein M is at least one of Fe, Co, Ni, Zn, Cu and Cr;
[0044] (2) calcining the M-Mg-Al ternary hydrotalcite;
[0045] (3) mixing the hydrotalcite material calcined in step (2) with an aqueous solution of a noble metal precursor, and then separating a solid material;
[0046] (4) calcining the solid material obtained in step (3);
[0047] (5) reducing the powder obtained after calcination in step (4).
[0048] In step (1), the M-Mg-Al ternary hydrotalcite is prepared by co-precipitation method. The precipitant used can be urea or a mixture of sodium carbonate and sodium hydroxide.
[0049] In step (1), in the process of preparing the M-Mg-Al ternary hydrotalcite, the metal salt precursor used may be nitrate and / or chloride, preferably nitrate.
[0050] In step (1), the synthesized hydrotalcite can be expressed as:
[0051]
[0052] Among them, M 2+ Can be Mg 2+ 、Ni 2+ 、Co 2+ 、Zn 2+ , Cu 2+ , M 3+ Can be Fe 3+ 、Al 3+ .
[0053] When a mixture of sodium carbonate and sodium hydroxide is used as a precipitant, the content of the alkali solution can be calculated by the following formula:
[0054] [OH - ]=2([Ni 2+ ]+[Mg 2+ ]+[Al 3+ ])
[0055] [CO 3 2- ]=0.5[Al 3+ ]
[0056] When urea is used as the precipitant, the concentration of urea in the solution may be 2-5 mol / L.
[0057] In a specific embodiment, when a mixture of sodium carbonate and sodium hydroxide is used as a precipitant, the specific operation process for preparing M-Mg-Al ternary hydrotalcite is as follows: a certain amount of Al(NO 3 ) 3 9H 2 O、Mg(NO 3 ) 2 6H 2O and M x+ (NO 3 ) x ·yH 2 O, denoted as solution A; dissolve a certain amount of Na 2 CO 3 (0.5-1.2mol / L) and NaOH (1-2mol / L), recorded as solution B; using a separatory funnel to add solution A and solution B dropwise into a three-necked flask placed in a 65°C water bath, and vigorously stirring the mixed solution in the three-necked flask; during the mixing process of solution A and solution B, the mixed solution is controlled to maintain a certain pH value by dropping NaOH solution (1-2mol / L) to completely precipitate the metal ions in the solution; after the mixing of solution A and solution B, the obtained mixed solution is continuously vigorously stirred in a 65°C water bath for 24 hours, and then the precipitated product is filtered and washed with deionized water, and the washed sample is dried in a forced air drying oven for 12 hours to obtain M-Mg-Al ternary hydrotalcite.
[0058] In another specific embodiment, when urea is used as a precipitant, the specific operation process for preparing M-Mg-Al ternary hydrotalcite is: a certain amount of M x+ (NO 3 ) x ·yH 2 O、Mg(NO 3 ) 2 6H 2 O、Al(NO 3 ) 3 9H 2 O and urea were dissolved in 300 mL of deionized water, where Mg 2+ 、Al 3+ 、M x+ The total concentration of the three types of metal cations is 0.15 mol / L, and the concentration of urea is 2-5 mol / L. The above solution is then placed in a 96°C water bath and vigorously stirred for 24 hours. After the stirring is completed, the obtained hydrotalcite dispersion is filtered and fully washed with deionized water until the pH value of the filtrate is neutral. Finally, the obtained hydrotalcite is dried to obtain M-Mg-Al ternary hydrotalcite.
[0059] In step (2), the calcination conditions may include: temperature of 200-500° C. and time of 3-6 hours.
[0060] In one specific embodiment, the specific operation process of calcining the M-Mg-Al ternary hydrotalcite is as follows: placing the M-Mg-Al ternary hydrotalcite in the center of a quartz boat, placing the quartz boat containing the sample in the center of the heating section of the quartz tube of a tube furnace, and heating the quartz boat in a protective gas (such as Ar or N 2) in the presence of a certain temperature at a constant heating rate from room temperature, and continue to calcine at a constant temperature for a period of time in an atmosphere of protective gas. After the calcination, the sample is naturally cooled to room temperature in an atmosphere of protective gas and sealed for storage for later use.
[0061] In step (3), the noble metal precursor may be at least one of chloroplatinic acid, platinum chloride, platinum nitrate, platinum acetylacetonate, palladium chloride, palladium nitrate and palladium acetate, preferably chloroplatinic acid and / or palladium nitrate.
[0062] Taking chloroplatinic acid as a noble metal precursor as an example, the present invention utilizes the "memory effect" of hydrotalcite to insert chloroplatinic acid ions into the interlayers of hydrotalcite. "Memory effect" refers to the structure of a hydrotalcite sample (at this time, the state of the sample is usually a composite oxide of metal ions in the hydrotalcite) roasted for a certain time at a certain temperature and added to a solution medium containing certain anions, and the structure can be partially restored to a hydrotalcite with an ordered layered structure. The method described in the present invention utilizes this effect to insert the negatively charged chloroplatinic acid anions generated after the hydrolysis of chloroplatinic acid into the interlayers of the hydrotalcite, and utilizes the charge attraction generated by the positively charged interlayers and the negatively charged intercalated chloroplatinic acid ions to make the platinum atoms uniformly arranged in the interlayers of the hydrotalcite.
[0063] In step (3), the concentration of the aqueous solution of the noble metal precursor may be 0.1-1 mmol / L, and most preferably 0.25 mmol / L.
[0064] In the method of the present invention, the specific operation process of step (3) can be: dispersing the hydrotalcite material in the aqueous solution of the noble metal precursor, adjusting the pH value of the obtained suspension to 5-9, then stirring in a constant temperature water bath for 5-48 hours, separating the solid, washing and drying. The temperature of the constant temperature water bath can be 60-90°C.
[0065] In a specific embodiment, the operation process of step (3) is: the calcined hydrotalcite material is uniformly dispersed in a chloroplatinic acid solution, and the pH of the suspension is adjusted to 5-9 using dilute hydrochloric acid (0.5 mol / L) or sodium hydroxide solution (0.5 mol / L); the suspension is then stirred in a 60-90°C water bath for 24 hours; after the stirring is completed, the suspension is washed with deionized water until neutral, and dried for standby use.
[0066] In the method described in the present invention, the specific operation of step (4) is: heating the solid material to 400-600° C. at a heating rate of 1-3° C. / min, and calcining for 3-6 hours.
[0067] In step (5), the reduction process is carried out in an atmosphere containing hydrogen and a protective gas, wherein the content of hydrogen in the atmosphere containing hydrogen and a carrier gas is 8-15 vol%. The protective gas may be an inert gas (such as Ar) or nitrogen.
[0068] In step (5), the reduction conditions may include: temperature of 300-500° C. and time of 1-3 h.
[0069] In the method described in the present invention, the amounts of various reaction raw materials are used so that in the prepared precious metal-based carbon monoxide oxidation catalyst, based on the total weight of the precious metal-based carbon monoxide oxidation catalyst, the content of Mg in terms of oxide is 10-40% by weight, preferably 25-40% by weight; the content of Al in terms of oxide is 20-60% by weight, preferably 40-60% by weight; the content of M in terms of oxide is 0.5-10% by weight, preferably 1-8% by weight; the content of Pt in terms of metal element is 0.1-1% by weight, preferably 0.5-0.8% by weight.
[0070] In the present invention, unless otherwise specified, the mass percentage of each component constituting the catalyst in the present invention refers to the mass percentage of the corresponding component in the mass of the catalyst. The content of each component in the gas composition used for catalyst reduction in the present invention refers to the volume percentage of the corresponding component in the total gas volume.
[0071] The present invention also provides a noble metal-based carbon monoxide oxidation catalyst prepared by the above method. The noble metal-based carbon monoxide oxidation catalyst has highly dispersed Pt / Pd-M alloy particles, and the alloy particles have a small average particle size and a unique surface structure, and a strong metal-support interaction is formed, so that the catalyst exhibits good catalytic activity in the carbon monoxide oxidation reaction, has a low activation temperature, and exhibits good catalytic stability in a hydrogen sulfide-containing atmosphere.
[0072] The present invention also provides the use of the above-mentioned noble metal-based carbon monoxide oxidation catalyst as a catalyst for carbon monoxide oxidation reaction. Specifically, the noble metal-based carbon monoxide oxidation catalyst of the present invention can be applied to a variety of low-concentration carbon monoxide removal conditions, especially a variety of low-concentration carbon monoxide removal conditions in the presence of sulfides. In a specific embodiment, the reaction raw gas used in the process of the carbon monoxide oxidation reaction contains sulfides below 50ppm.
[0073] Relying on the precious metal-based carbon monoxide oxidation catalyst described in the present invention, a low-concentration carbon monoxide catalytic removal technology can be formed, which is suitable for a variety of low-concentration carbon monoxide removal conditions including the presence of sulfides, and can reduce the carbon monoxide concentration in the exhaust gas to below 50ppm. It can be widely used in exhaust gas treatment in petrochemical, steel, industrial kilns, waste incineration and other processes, and is of great significance for protecting the atmospheric environment and ensuring human health.
[0074] The following examples further illustrate the noble metal-based carbon monoxide oxidation catalyst and its preparation method and application. The examples are implemented based on the technical solution of the present invention, and provide detailed implementation methods and specific operation processes, but the protection scope of the present invention is not limited to the following examples.
[0075] The experimental methods in the following examples, unless otherwise specified, are all conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, are all commercially available.
[0076] Example 1
[0077] The 3.64 g Fe(NO 3 ) 3 9H 2 O, 3.84 g Mg(NO 3 ) 2 6H 2 O, 7.88gAl(NO 3 ) 3 9H 2 O and 36.0 g urea were dissolved in 300.0 mL deionized water, of which Mg 2+ 、Al 3+ , Fe 3+ The total concentration of the three metal cations was 0.15 mol / L, the urea concentration was 2.0 mol / L, and the above solution was then placed in a 96°C water bath and stirred vigorously for 24 hours. After stirring, the obtained hydrotalcite dispersion was filtered and fully washed with deionized water until the pH value of the filtrate was neutral; finally, the obtained hydrotalcite was dried, and the product was named FeMgAl-LDH.
[0078] The FeMgAl-LDH powder obtained above was placed in the center of a quartz boat, and the quartz boat containing the sample was placed in the center of the heating section of the quartz tube of a tubular furnace. The FeMgAl-LDH powder was heated from room temperature to 300°C at a rate of 1°C / min under the protection of an inert gas argon gas flow, and was calcined at a constant temperature for a period of time in an inert atmosphere. After the calcination, the sample was naturally cooled to room temperature under the protection of an argon atmosphere, and sealed and stored for later use.
[0079] Prepare a 0.25 mmol / L chloroplatinic acid solution and let it stand for later use.
[0080] 2 g of the calcined hydrotalcite material was uniformly dispersed in 60 mL of chloroplatinic acid solution, and the pH of the suspension was adjusted to 8 with a sodium hydroxide solution (0.5 mol / L). Subsequently, the suspension was stirred in a water bath at a certain temperature for 24 h. After the stirring was completed, it was washed with deionized water until neutral, and dried for standby use.
[0081] The material obtained above was heated to 500°C at a heating rate of 1°C / min and calcined in air for 4 h.
[0082] The calcined powder was placed in a tube furnace under 10 vol% H 2 / Ar atmosphere, the temperature was raised to 500 °C at a constant heating rate and then reduced for 2 h. After the reduction was completed, the 2 / Ar atmosphere was cooled to room temperature to obtain a Pt-based carbon monoxide oxidation catalyst, which was abbreviated as PtFe / MgAlO x .
[0083] ICP-OES characterization revealed that the catalyst PtFe / MgAlO x In the invention, based on the total weight, the content of Mg in terms of oxide is 33.11 wt %, the content of Al in terms of oxide is 59.91 wt %, the content of Fe in terms of oxide is 6.47 wt %, and the content of Pt in terms of metal element is 0.51 wt %.
[0084] The catalyst PtFe / MgAlO x The SEM and TEM images are as follows Figure 2 shown.
[0085] The results of scanning transmission electron microscopy (STEM-HAADF) and high-resolution transmission electron microscopy (HRTEM) were obtained (see Figure 3 ) It can be seen that the catalyst PtFe / MgAlO x The Pt exists in the form of Pt-Fe alloy particles, and the average particle size of the Pt-Fe alloy particles is 7 nm.
[0086] The prepared catalyst PtFe / MgAlO x Placed in a fixed bed microreactor, the inner diameter of the reaction tube is 6 mm. The temperature is raised to 250°C at a rate of 5°C / min and the reaction raw gas composition is 0.6 vol% CO / 0.005 vol% H 2 S / 5vol%O 2 / 94.395vol%CO 2 , control the reaction space velocity to 10000h-1 The CO concentration at the reactor outlet was detected by gas chromatograph. x The reaction results of catalytic oxidation CO conversion rate are as follows Figure 1 As shown, from Figure 1 It can be seen that during the 200h long-cycle carbon monoxide oxidation reaction, the carbon monoxide conversion rate is maintained above 99%.
[0087] Example 2
[0088] The 2.62 g Ni(NO 3 ) 2 6H 2 O, 3.84 g Mg(NO 3 ) 2 6H 2 O, 7.88gAl(NO 3 ) 3 9H 2 O and 36.0 g urea were dissolved in 300.0 mL deionized water, of which Mg 2+ 、Al 3+ 、Ni 2+ The total concentration of the three metal cations was 0.15 mol / L, the urea concentration was 2.0 mol / L, and the above solution was then placed in a 96°C water bath and stirred vigorously for 24 hours. After stirring, the obtained hydrotalcite dispersion was filtered and fully washed with deionized water until the pH value of the filtrate was neutral; finally, the obtained hydrotalcite was dried, and the product was named NiMgAl-LDH.
[0089] The NiMgAl-LDH powder obtained above was placed in the center of a quartz boat, and the quartz boat containing the sample was placed in the center of the heating section of the quartz tube of a tubular furnace. The NiMgAl-LDH powder was heated from room temperature to 350°C at a rate of 1°C / min under the protection of an inert gas argon gas flow, and was calcined continuously at a constant temperature for a period of time in an argon atmosphere. After the calcination, the sample was naturally cooled to room temperature under the protection of an argon atmosphere, and sealed and stored for later use.
[0090] Prepare a 0.25 mmol / L chloroplatinic acid solution and let it stand for later use.
[0091] Take 2g of the calcined hydrotalcite material and evenly disperse it in 60mL of chloroplatinic acid solution, and adjust the pH of the suspension to 8.5 with sodium hydroxide solution (0.5mol / L). Then, stir the suspension in a water bath at a certain temperature for 24h. After stirring, wash with deionized water until neutral, and dry for standby use.
[0092] The material obtained above was heated to 500°C at a heating rate of 1°C / min and calcined in air for 4 h.
[0093] The calcined powder was placed in a tube furnace under 10 vol% H 2 / Ar atmosphere, the temperature was raised to 500 °C at a constant heating rate and then reduced for 2 h. After the reduction was completed, the 2 / Ar atmosphere was cooled to room temperature to obtain a Pt-based carbon monoxide oxidation catalyst, which was abbreviated as PtNi / MgAlO x .
[0094] ICP-OES characterization revealed that the catalyst PtNi / MgAlO x In the invention, based on the total weight, the content of Mg in terms of oxide is 37.03 wt %, the content of Al in terms of oxide is 55.03 wt %, the content of Ni in terms of oxide is 6.96 wt %, and the content of Pt in terms of metal element is 0.98 wt %.
[0095] The results of scanning transmission electron microscopy (STEM-HAADF) and high-resolution transmission electron microscopy (HRTEM) show that the catalyst PtNi / MgAlO x The Pt exists in the form of Pt-Ni alloy particles, and the average particle size of the Pt-Ni alloy particles is 8 nm.
[0096] The prepared catalyst PtNi / MgAlO x Placed in a fixed bed microreactor, the inner diameter of the reaction tube is 6 mm. The temperature is raised to 250°C at a rate of 5°C / min and the reaction raw gas composition is 0.6 vol% CO / 0.005 vol% H 2 S / 5vol%O 2 / 94.395vol%CO 2 , control the reaction space velocity to 10000h -1 The CO concentration at the reactor outlet was detected by gas chromatography. The reaction results show that the carbon monoxide conversion rate was maintained above 99% during the 200h long-term carbon monoxide oxidation reaction.
[0097] Example 3
[0098] Dissolve 2.62 g Co(NO 3 ) 2 6H 2 O, 3.84 g Mg(NO 3 ) 2 6H 2 O, 7.88gAl(NO 3 )3 9H 2 O, recorded as solution A. Dissolve 12.75 g of Na 2 CO 3 (0.8mol / L) and 6gNaOH (1.0mol / L), recorded as solution B. Use a separatory funnel to add solution A and solution B dropwise into a three-necked flask placed in a 65°C water bath, and vigorously stir the mixed solution in the three-necked flask. During the mixing process of solution A and solution B, the pH value of the mixed solution is controlled to be 10.5 by dropping NaOH solution (2.0mol / L) to completely precipitate the metal ions in the solution. After the A and B solutions are mixed, the resulting mixed solution is continued to be vigorously stirred in a 65°C water bath for 24 hours, and then the precipitated product is filtered and washed with deionized water. The washed sample is dried in a forced air drying oven for 12 hours, and the resulting hydrotalcite sample is recorded as CoMgAl-LDH.
[0099] The CoMgAl-LDH powder obtained above was placed in the center of a quartz boat, and the quartz boat containing the sample was placed in the center of the heating section of the quartz tube of a tubular furnace. The CoMgAl-LDH powder was heated from room temperature to 300°C at a rate of 1°C / min under the protection of an inert gas argon gas flow, and was calcined continuously at a constant temperature for a period of time in an argon atmosphere. After the calcination, the sample was naturally cooled to room temperature under the protection of an argon atmosphere, and sealed and stored for later use.
[0100] Prepare a 0.25 mmol / L chloroplatinic acid solution and let it stand for later use.
[0101] Take 2g of the calcined hydrotalcite material and evenly disperse it in 60mL of chloroplatinic acid solution, and adjust the pH of the suspension to 6.0 with a dilute hydrochloric acid solution (0.5mol / L). Then, stir the suspension in a water bath at a certain temperature for 24h. After stirring, wash with deionized water until neutral, and dry for standby use.
[0102] The material obtained above was heated to 500°C at a heating rate of 1°C / min and calcined in air for 4 h.
[0103] The calcined powder was placed in a tube furnace under 10 vol% H 2 / Ar atmosphere, the temperature was raised to 500 °C at a constant heating rate and then reduced for 2 h. After the reduction was completed, the 2 / Ar atmosphere was cooled to room temperature to obtain a Pt-based carbon monoxide oxidation catalyst, which was abbreviated as PtCo / MgAlO x .
[0104] ICP-OES detection shows that the catalyst PtCo / MgAlO xIn the composite, based on the total weight, the content of Mg in terms of oxide is 35.34 wt %, the content of Al in terms of oxide is 59.62 wt %, the content of Co in terms of oxide is 4.13 wt %, and the content of Pt in terms of metal element is 0.91 wt %.
[0105] The results of scanning transmission electron microscopy (STEM-HAADF) and high-resolution transmission electron microscopy (HRTEM) showed that the catalyst PtCo / MgAlO x The Pt exists in the form of Pt-Co alloy particles, and the average particle size of the Pt-Co alloy particles is 4 nm.
[0106] The prepared catalyst PtCo / MgAlO x Placed in a fixed bed microreactor, the inner diameter of the reaction tube is 6 mm. The temperature is raised to 250°C at a rate of 5°C / min and the reaction raw gas composition is 0.6 vol% CO / 0.005 vol% H 2 S / 5vol%O 2 / 94.395vol%CO 2 , control the reaction space velocity to 10000h -1 The CO concentration at the reactor outlet was detected by gas chromatography. The reaction results show that the carbon monoxide conversion rate was maintained above 99% during the 200h long-term carbon monoxide oxidation reaction.
[0107] Example 4
[0108] The 3.64 g Fe(NO 3 ) 3 9H 2 O, 3.84 g Mg(NO 3 ) 2 6H 2 O, 7.88gAl(NO 3 ) 3 9H 2 O and 36.0 g urea were dissolved in 300.0 mL deionized water, of which Mg 2+ 、Al 3+ , Fe 3+ The total concentration of the three metal cations was 0.15 mol / L, the urea concentration was 2.0 mol / L, and the above solution was then placed in a 96°C water bath and stirred vigorously for 24 hours. After stirring, the obtained hydrotalcite dispersion was filtered and fully washed with deionized water until the pH value of the filtrate was neutral; finally, the obtained hydrotalcite was dried, and the product was named FeMgAl-LDH.
[0109] The FeMgAl-LDH powder obtained above was placed in the center of a quartz boat, and the quartz boat containing the sample was placed in the center of the heating section of the quartz tube of a tubular furnace. The FeMgAl-LDH powder was heated from room temperature to 300°C at a rate of 1°C / min under the protection of an inert gas argon gas flow, and was calcined at a constant temperature for a period of time in an inert atmosphere. After the calcination, the sample was naturally cooled to room temperature under the protection of an argon atmosphere, and sealed and stored for later use.
[0110] Prepare a 0.25 mmol / L chloroplatinic acid solution and let it stand for later use.
[0111] 2 g of the calcined hydrotalcite material was uniformly dispersed in 70 mL of chloroplatinic acid solution, and the pH of the suspension was adjusted to 8 with a sodium hydroxide solution (0.5 mol / L). Subsequently, the suspension was stirred in a water bath at a certain temperature for 24 h. After the stirring was completed, it was washed with deionized water until neutral, and dried for standby use.
[0112] The material obtained above was heated to 400°C at a heating rate of 2°C / min and calcined in air for 6 h.
[0113] The calcined powder was placed in a tube furnace under 10 vol% H 2 / Ar atmosphere, the temperature was raised to 500 °C at a constant heating rate and then reduced for 2 h. After the reduction was completed, the 2 / Ar atmosphere was cooled to room temperature to obtain a Pt-based carbon monoxide oxidation catalyst, which was abbreviated as PtFe / MgAlO x .
[0114] ICP-OES characterization revealed that the catalyst PtFe / MgAlO x In the invention, based on the total weight, the content of Mg in terms of oxide is 33.06 wt %, the content of Al in terms of oxide is 59.80 wt %, the content of Fe in terms of oxide is 6.46 wt %, and the content of Pt in terms of metal element is 0.68 wt %.
[0115] The results of scanning transmission electron microscopy (STEM-HAADF) and high-resolution transmission electron microscopy (HRTEM) showed that the catalyst PtFe / MgAlO x The Pt exists in the form of Pt-Fe alloy particles, and the average particle size of the Pt-Fe alloy particles is 7 nm.
[0116] The prepared catalyst PtFe / MgAlO x Placed in a fixed bed microreactor, the inner diameter of the reaction tube is 6 mm. The temperature is raised to 250°C at a rate of 5°C / min and the reaction raw gas composition is 0.6 vol% CO / 0.005 vol% H2 S / 5vol%O 2 / 94.395vol%CO 2 , control the reaction space velocity to 10000h -1 The CO concentration at the reactor outlet was detected by gas chromatography. The reaction results show that the carbon monoxide conversion rate was maintained above 99% during the 200h long-term carbon monoxide oxidation reaction.
[0117] Example 5
[0118] The 3.64 g Fe(NO 3 ) 3 9H 2 O, 3.84 g Mg(NO 3 ) 2 6H 2 O, 7.88gAl(NO 3 ) 3 9H 2 O and 36.0 g urea were dissolved in 300.0 mL deionized water, of which Mg 2+ 、Al 3+ , Fe 3+ The total concentration of the three metal cations was 0.15 mol / L, the urea concentration was 2.0 mol / L, and the above solution was then placed in a 96°C water bath and stirred vigorously for 24 hours. After stirring, the obtained hydrotalcite dispersion was filtered and fully washed with deionized water until the pH value of the filtrate was neutral; finally, the obtained hydrotalcite was dried, and the product was named FeMgAl-LDH.
[0119] The FeMgAl-LDH powder obtained above was placed in the center of a quartz boat, and the quartz boat containing the sample was placed in the center of the heating section of the quartz tube of a tubular furnace. The FeMgAl-LDH powder was heated from room temperature to 300°C at a rate of 1°C / min under the protection of an inert gas argon gas flow, and was calcined at a constant temperature for a period of time in an inert atmosphere. After the calcination, the sample was naturally cooled to room temperature under the protection of an argon atmosphere, and sealed and stored for later use.
[0120] Prepare a 0.25 mmol / L chloroplatinic acid solution and let it stand for later use.
[0121] 2 g of the calcined hydrotalcite material was uniformly dispersed in 80 mL of chloroplatinic acid solution, and the pH of the suspension was adjusted to 8 with a sodium hydroxide solution (0.5 mol / L). Subsequently, the suspension was stirred in a water bath at a certain temperature for 24 h. After the stirring was completed, it was washed with deionized water until neutral, and dried for standby use.
[0122] The material obtained above was heated to 600°C at a heating rate of 3°C / min and calcined in air for 3 h.
[0123] The calcined powder was placed in a tube furnace under 10 vol% H 2 / Ar atmosphere, the temperature was raised to 500 °C at a constant heating rate and then reduced for 2 h. After the reduction was completed, the 2 / Ar atmosphere was cooled to room temperature to obtain a Pt-based carbon monoxide oxidation catalyst, which was abbreviated as PtFe / MgAlO x .
[0124] ICP-OES characterization revealed that the catalyst PtFe / MgAlO x In the invention, based on the total weight, the content of Mg in terms of oxide is 33.03 wt %, the content of Al in terms of oxide is 59.74 wt %, the content of Fe in terms of oxide is 6.46 wt %, and the content of Pt in terms of metal element is 0.77 wt %.
[0125] The results of scanning transmission electron microscopy (STEM-HAADF) and high-resolution transmission electron microscopy (HRTEM) showed that the catalyst PtFe / MgAlO x The Pt exists in the form of Pt-Fe alloy particles, and the average particle size of the Pt-Fe alloy particles is 7 nm.
[0126] The prepared catalyst PtFe / MgAlO x Placed in a fixed bed microreactor, the inner diameter of the reaction tube is 6 mm. The temperature is raised to 250°C at a rate of 5°C / min and the reaction raw gas composition is 0.6 vol% CO / 0.005 vol% H 2 S / 5vol%O 2 / 94.395vol%CO 2 , control the reaction space velocity to 10000h -1 The CO concentration at the reactor outlet was detected by gas chromatography. The reaction results show that the carbon monoxide conversion rate was maintained above 99% during the 200h long-term carbon monoxide oxidation reaction.
[0127] Example 6
[0128] The 2.62 g Ni(NO 3 ) 2 6H 2 O, 3.84 g Mg(NO 3 ) 2 6H 2 O, 7.88gAl(NO 3 )3 9H 2 O and 36.0 g urea were dissolved in 300.0 mL deionized water, of which Mg 2+ 、Al 3+ 、Ni 2+ The total concentration of the three metal cations was 0.15 mol / L, the urea concentration was 2.0 mol / L, and the above solution was then placed in a 96°C water bath and stirred vigorously for 24 hours. After stirring, the obtained hydrotalcite dispersion was filtered and fully washed with deionized water until the pH value of the filtrate was neutral; finally, the obtained hydrotalcite was dried, and the product was named NiMgAl-LDH.
[0129] The NiMgAl-LDH powder obtained above was placed in the center of a quartz boat, and the quartz boat containing the sample was placed in the center of the heating section of the quartz tube of a tubular furnace. The NiMgAl-LDH powder was heated from room temperature to 350°C at a rate of 1°C / min under the protection of an inert gas argon gas flow, and was calcined continuously at a constant temperature for a period of time in an argon atmosphere. After the calcination, the sample was naturally cooled to room temperature under the protection of an argon atmosphere, and sealed and stored for later use.
[0130] Prepare a 0.25 mmol / L chloroplatinic acid solution and let it stand for later use.
[0131] 2 g of the calcined hydrotalcite material was uniformly dispersed in 55 mL of chloroplatinic acid solution, and the pH of the suspension was adjusted to 8.5 using a sodium hydroxide solution (0.5 mol / L). Subsequently, the suspension was stirred in a water bath at a certain temperature for 24 h. After stirring, it was washed with deionized water until neutral, and dried for standby use.
[0132] The material obtained above was heated to 400°C at a heating rate of 2°C / min and calcined in air for 4 h.
[0133] The calcined powder was placed in a tube furnace under 10 vol% H 2 / Ar atmosphere, the temperature was raised to 500 °C at a constant heating rate and then reduced for 2 h. After the reduction was completed, the 2 / Ar atmosphere was cooled to room temperature to obtain a Pt-based carbon monoxide oxidation catalyst, which was abbreviated as PtNi / MgAlO x .
[0134] ICP-OES characterization revealed that the catalyst PtNi / MgAlO x In the invention, based on the total weight, the content of Mg in terms of oxide is 37.10 wt %, the content of Al in terms of oxide is 55.15 wt %, the content of Ni in terms of oxide is 6.97 wt %, and the content of Pt in terms of metal element is 0.78 wt %.
[0135] The results of scanning transmission electron microscopy (STEM-HAADF) and high-resolution transmission electron microscopy (HRTEM) show that the catalyst PtNi / MgAlO x The Pt exists in the form of Pt-Ni alloy particles, and the average particle size of the Pt-Ni alloy particles is 8 nm.
[0136] The prepared catalyst PtNi / MgAlO x Placed in a fixed bed microreactor, the inner diameter of the reaction tube is 6 mm. The temperature is raised to 250°C at a rate of 5°C / min and the reaction raw gas composition is 0.6 vol% CO / 0.005 vol% H 2 S / 5vol%O 2 / 94.395vol%CO 2 , control the reaction space velocity to 10000h -1 The CO concentration at the reactor outlet was detected by gas chromatography. The reaction results show that the carbon monoxide conversion rate was maintained above 99% during the 200h long-term carbon monoxide oxidation reaction.
[0137] Example 7
[0138] The 2.62 g Ni(NO 3 ) 2 6H 2 O, 3.84 g Mg(NO 3 ) 2 6H 2 O, 7.88gAl(NO 3 ) 3 9H 2 O and 36.0 g urea were dissolved in 300.0 mL deionized water, of which Mg 2+ 、Al 3+ 、Ni 2+ The total concentration of the three metal cations was 0.15 mol / L, the urea concentration was 2.0 mol / L, and the above solution was then placed in a 96°C water bath and stirred vigorously for 24 hours. After stirring, the obtained hydrotalcite dispersion was filtered and fully washed with deionized water until the pH value of the filtrate was neutral; finally, the obtained hydrotalcite was dried, and the product was named NiMgAl-LDH.
[0139] The NiMgAl-LDH powder obtained above was placed in the center of a quartz boat, and the quartz boat containing the sample was placed in the center of the heating section of the quartz tube of a tubular furnace. The NiMgAl-LDH powder was heated from room temperature to 350°C at a rate of 1°C / min under the protection of an inert gas argon gas flow, and was calcined continuously at a constant temperature for a period of time in an argon atmosphere. After the calcination, the sample was naturally cooled to room temperature under the protection of an argon atmosphere, and sealed and stored for later use.
[0140] Prepare a 0.25 mmol / L chloroplatinic acid solution and let it stand for later use.
[0141] Take 2g of the calcined hydrotalcite material and evenly disperse it in 50mL of chloroplatinic acid solution, and adjust the pH of the suspension to 8.5 with sodium hydroxide solution (0.5mol / L). Then, stir the suspension in a water bath at a certain temperature for 24h. After stirring, wash it with deionized water until it is neutral, and dry it for standby use.
[0142] The material obtained above was heated to 500°C at a heating rate of 1°C / min and calcined in air for 4 h.
[0143] The calcined powder was placed in a tube furnace under 10 vol% H 2 / Ar atmosphere, the temperature was raised to 500 °C at a constant heating rate and then reduced for 2 h. After the reduction was completed, the 2 / Ar atmosphere was cooled to room temperature to obtain a Pt-based carbon monoxide oxidation catalyst, which was abbreviated as PtNi / MgAlO x .
[0144] ICP-OES characterization revealed that the catalyst PtNi / MgAlO x In the invention, based on the total weight, the content of Mg in terms of oxide is 37.15 wt %, the content of Al in terms of oxide is 55.22 wt %, the content of Ni in terms of oxide is 6.98 wt %, and the content of Pt in terms of metal element is 0.65 wt %.
[0145] The results of scanning transmission electron microscopy (STEM-HAADF) and high-resolution transmission electron microscopy (HRTEM) show that the catalyst PtNi / MgAlO x The Pt exists in the form of Pt-Ni alloy particles, and the average particle size of the Pt-Ni alloy particles is 8 nm.
[0146] The prepared catalyst PtNi / MgAlO x Placed in a fixed bed microreactor, the inner diameter of the reaction tube is 6 mm. The temperature is raised to 250°C at a rate of 5°C / min and the reaction raw gas composition is 0.6 vol% CO / 0.005 vol% H2 S / 5vol%O 2 / 94.395vol%CO 2 , control the reaction space velocity to 10000h -1 The CO concentration at the reactor outlet was detected by gas chromatography. The reaction results show that the carbon monoxide conversion rate was maintained above 99% during the 200h long-term carbon monoxide oxidation reaction.
[0147] Example 8
[0148] Dissolve 2.62 g Co(NO 3 ) 2 6H 2 O, 3.84 g Mg(NO 3 ) 2 6H 2 O, 7.88gAl(NO 3 ) 3 9H 2 O, recorded as solution A. Dissolve 12.75 g of Na 2 CO 3 (0.8mol / L) and 6gNaOH (1.0mol / L), recorded as solution B. Use a separatory funnel to add solution A and solution B dropwise into a three-necked flask placed in a 65°C water bath, and vigorously stir the mixed solution in the three-necked flask. During the mixing process of solution A and solution B, the pH value of the mixed solution is controlled to be 10.5 by dropping NaOH solution (2.0mol / L) to completely precipitate the metal ions in the solution. After the A and B solutions are mixed, the resulting mixed solution is continued to be vigorously stirred in a 65°C water bath for 24 hours, and then the precipitated product is filtered and washed with deionized water. The washed sample is dried in a forced air drying oven for 12 hours, and the resulting hydrotalcite sample is recorded as CoMgAl-LDH.
[0149] The CoMgAl-LDH powder obtained above was placed in the center of a quartz boat, and the quartz boat containing the sample was placed in the center of the heating section of the quartz tube of a tubular furnace. The CoMgAl-LDH powder was heated from room temperature to 300°C at a rate of 1°C / min under the protection of an inert gas argon gas flow, and was calcined continuously at a constant temperature for a period of time in an argon atmosphere. After the calcination, the sample was naturally cooled to room temperature under the protection of an argon atmosphere, and sealed and stored for later use.
[0150] Prepare a 0.25 mmol / L chloroplatinic acid solution and let it stand for later use.
[0151] Take 2g of the calcined hydrotalcite material and evenly disperse it in 55mL of chloroplatinic acid solution, and adjust the pH of the suspension to 6.0 with a dilute hydrochloric acid solution (0.5mol / L). Then, stir the suspension in a water bath at a certain temperature for 24h. After stirring, wash it with deionized water until it is neutral, and dry it for standby use.
[0152] The material obtained above was heated to 600°C at a heating rate of 3°C / min and calcined in air for 4 h.
[0153] The calcined powder was placed in a tube furnace under 10 vol% H 2 / Ar atmosphere, the temperature was raised to 500 °C at a constant heating rate and then reduced for 2 h. After the reduction was completed, the 2 / Ar atmosphere was cooled to room temperature to obtain a Pt-based carbon monoxide oxidation catalyst, which was abbreviated as PtCo / MgAlO x .
[0154] ICP-OES detection shows that the catalyst PtCo / MgAlO x In the invention, based on the total weight, the content of Mg in terms of oxide is 35.40 wt %, the content of Al in terms of oxide is 59.72 wt %, the content of Co in terms of oxide is 4.13 wt %, and the content of Pt in terms of metal element is 0.75 wt %.
[0155] The results of scanning transmission electron microscopy (STEM-HAADF) and high-resolution transmission electron microscopy (HRTEM) showed that the catalyst PtCo / MgAlO x The Pt exists in the form of Pt-Co alloy particles, and the average particle size of the Pt-Co alloy particles is 4 nm.
[0156] The prepared catalyst PtCo / MgAlO x Placed in a fixed bed microreactor, the inner diameter of the reaction tube is 6 mm. The temperature is raised to 250°C at a rate of 5°C / min and the reaction raw gas composition is 0.6 vol% CO / 0.005 vol% H 2 S / 5vol%O 2 / 94.395vol%CO 2 , control the reaction space velocity to 10000h -1 The CO concentration at the reactor outlet was detected by gas chromatography. The reaction results show that the carbon monoxide conversion rate was maintained above 99% during the 200h long-term carbon monoxide oxidation reaction.
[0157] Comparative Examples 1-3
[0158] The preparation methods of Comparative Examples 1, 2, and 3 correspond to Examples 1, 2, and 3, respectively. The method for preparing the hydrotalcite carrier is the same, but the difference is that the method for loading Pt is different from that of Examples 1-3. The platinum precursor chloroplatinic acid solution is directly loaded by an equal volume impregnation method. The impregnation steps are briefly described as follows using Comparative Example 1 as an example:
[0159] Determination of saturated water absorption rate: Weigh 1g of the calcined FeMgAl-LDH carrier, add it to a 5mL measuring cylinder, and after knocking it on a flat surface, read the dense volume as 0.8mL. After adding 2mL of water, stir it thoroughly and let it stand for 12h. Read the volume of the mixed solution as 2.0mL. The saturated water absorption rate of the FeMgAl carrier is calculated to be 0.8mL / g.
[0160] Weigh 1.52g of the prepared chloroplatinic acid solution into a 50mL beaker, add 6.5mL of deionized water, and stir thoroughly to dissolve. Then, add 10g of FeMgAl carrier and stir for 0.5h at room temperature to obtain a slurry mixture. Seal the beaker containing the mixture with a sealing film. Place in a cool and dry place and let stand for 12h.
[0161] The subsequent drying and roasting operation methods and conditions are consistent with those in the embodiment.
[0162] It can be seen from the transmission electron microscopy that the catalysts prepared in the above comparative examples 1-3 do not form uniform small-sized alloy particles. Taking the catalyst prepared in comparative example 1 as an example, the TEM characterization results are as follows: Figure 4 As shown, from Figure 4 It can be seen that the average particle size of the metal particles on the catalyst is 40 nm, which is much larger than the catalyst prepared in the above example.
[0163] The comparison of the reaction activity evaluation of Examples 1-8 and Comparative Examples 1-3 is shown in Table 1, wherein T50 and T90 refer to the lowest temperatures at which the conversion rate reaches 50% and 90%, respectively.
[0164] Table 1
[0165]
[0166]
[0167] It can be seen from the data in Table 1 that the noble metal-based carbon monoxide oxidation catalyst according to the present invention can still stably carry out the carbon monoxide oxidation removal process in the presence of hydrogen sulfide, and can take into account both catalytic oxidation activity and sulfur-resistant reaction stability.
[0168] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A noble metal-based carbon monoxide oxidation catalyst comprising a carrier and an active component supported on the carrier, characterized in that: The active component is Pt and / or Pd, and the carrier is formed by calcining and reducing M-Mg-Al ternary hydrotalcite, wherein M is at least one of Fe, Co, Ni, Zn, Cu and Cr, and Pt and / or Pd form alloy particles with M.
2. The noble metal-based carbon monoxide oxidation catalyst according to claim 1, characterized in that: Based on the total weight of the noble metal-based carbon monoxide oxidation catalyst, the content of Mg in terms of oxide is 10-40 wt %, the content of Al in terms of oxide is 20-60 wt %, the content of M in terms of oxide is 0.5-10 wt %, and the content of Pt and / or Pd in terms of metal elements is 0.1-1 wt %.
3. A method for preparing a noble metal-based carbon monoxide oxidation catalyst, characterized in that: The method comprises the following steps: (1) preparing M-Mg-Al ternary hydrotalcite, wherein M is at least one of Fe, Co, Ni, Zn, Cu and Cr; (2) calcining the M-Mg-Al ternary hydrotalcite; (3) mixing the hydrotalcite material calcined in step (2) with an aqueous solution of a noble metal precursor, and then separating a solid material; (4) calcining the solid material obtained in step (3); (5) reducing the powder obtained after calcination in step (4).
4. The method according to claim 3, characterized in that In step (1), the M-Mg-Al ternary hydrotalcite is prepared by a co-precipitation method.
5. The method according to claim 4, characterized in that The precipitant used is urea or a mixture of sodium carbonate and sodium hydroxide.
6. The method according to claim 4 or 5, characterized in that: The metal salt precursor used is nitrate and / or chloride, preferably nitrate.
7. The method according to claim 3, characterized in that In step (2), the calcination conditions include: temperature of 200-500° C. and time of 3-6 hours.
8. The method according to claim 3, characterized in that In step (3), the noble metal precursor is at least one of chloroplatinic acid, platinum chloride, platinum nitrate, platinum acetylacetonate, palladium chloride, palladium nitrate and palladium acetate.
9. The method according to claim 3 or 8, characterized in that: The specific operation process of step (3) is: dispersing the hydrotalcite material in the aqueous solution of the noble metal precursor, adjusting the pH value of the obtained suspension to 5-9, then stirring in a constant temperature water bath for 5-48 hours, separating the solid, washing and drying; Preferably, the temperature of the constant temperature water bath is 60-90°C.
10. The method according to claim 3, characterized in that: The specific operation of step (4) is: heating the solid material to 400-600° C. at a heating rate of 1-3° C. / min, and calcining for 3-6 hours.
11. The method according to claim 3, characterized in that In step (5), the reduction process is carried out in an atmosphere containing hydrogen and a protective gas, wherein the content of hydrogen in the atmosphere containing hydrogen and a carrier gas is 8-15 vol%; Preferably, the reduction conditions include: temperature of 300-500° C. and time of 1-3 h.
12. A noble metal-based carbon monoxide oxidation catalyst prepared by the method according to any one of claims 3 to 11.
13. Use of the noble metal-based carbon monoxide oxidation catalyst according to claim 1, 2 or 12 as a catalyst for carbon monoxide oxidation reaction.
14. The use according to claim 13, characterized in that The reaction raw gas used in the carbon monoxide oxidation reaction contains sulfides below 50 ppm.
Citation Information
Patent Citations
Preparation method of palladium catalyst suitable for water-vapor coexisting carbon oxide oxidization
CN106881110A
A modularly structured gold catalyst, its preparation method and application
CN107649129B
Quadruple effect catalyst of diesel tail gas and preparation method and application of quadruple effect catalyst
CN102188971A
Monatomic catalyst based on hydrotalcite structure and preparation method thereof
CN111389416A
Catalyst for low temperature elimination of CO and its prepn process
CN1974004A